2009
DOI: 10.1007/s12088-009-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of neuraminidase (NA) inhibitors against H1N1 strains of different geographical regions: an in silico approach

Abstract: This report described the effi cacy of NA inhibitors against newly evolved strains of H1N1 viruses. This in silico study was designed to understand the mode of interactions of NA inhibitors with NA. Hence, ligand, oseltamivir, zanamivir and peramivir were docked with modeled NA, ACD65204 (USA/2007), BAA06717 (Japan/1992), ACE77988 (S. Korea/2005) and ACD65204 (USA/2007). This study is based on interaction energies. Ramachandran Z-scores for these modeled structures were found to be -0.998, -1.121, -0.870 and -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This was strongly supported by the experimental studies that suggested a better activity of doripenem over other carbapenems against carbapenemase producing bacteria [19]. Moreover, in a similar 2009 study authors have used interaction energies of docking to compare the efficacy of different neuraminidase inhibitors against newly evolved strains of H1N1 viruses [20]. It is important to mention here that more experimental studies are needed to establish a precise relationship between MIC and interaction energy.…”
Section: Discussionmentioning
confidence: 80%
“…This was strongly supported by the experimental studies that suggested a better activity of doripenem over other carbapenems against carbapenemase producing bacteria [19]. Moreover, in a similar 2009 study authors have used interaction energies of docking to compare the efficacy of different neuraminidase inhibitors against newly evolved strains of H1N1 viruses [20]. It is important to mention here that more experimental studies are needed to establish a precise relationship between MIC and interaction energy.…”
Section: Discussionmentioning
confidence: 80%
“…In earlier studies it has also been observed that the calculated binding free energy values are with inverse proportional to the corresponding MIC values for enzyme-drug complexes [ 15 ]. Moreover, previously, authors have used interaction energies of docking to compare the efficacy of different neuraminidase inhibitors against newly evolved strains of H1N1 viruses [ 16 ]. Our data is consistent with the earlier studies [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although oseltamivir and zanamivir are the best drugs for the prophylaxis and treatment of inuenza infections, the emergence of drug-resistant variants is a major problem in antiviral therapy. 9 The NA-R292K mutation has been isolated from (A/Shanghai/1/2013) H7N9 inuenza virus. Viruses with this mutation cause reduced sensitivity to oseltamivir and zanamivir.…”
Section: Introductionmentioning
confidence: 99%